IMPACT OF EARNING PER SHARE AND PRICE EARNINGS RATIO ON MARKET PRICE OF SHARE: A STUDY ON AUTO SECTOR IN INDIA - Kumar, Pankaj (International Journal of Research -GRANTHAALAYAH, 2017)
The purpose of this study is to examine the impact of earning per share and price earnings ratio on the market price of share of company, therefore in this study market price of share is dependent variable, while earning per share and price earnings ratio are dependent variables and study is exploratory in nature. The study was carried out for a sample of eight companies of auto sector based on Nifty auto index and for a period of five consecutive financial years from 2011-12 to 2015-16. Multiple regression analysis was employed to predict the impact of earning per share and price earnings ratio on market price of share of select companies of auto sector. The result of the study concludes that earning per share has found to be a very strong forecaster of market price of share, while price earnings ratio impact significantly on the prediction of market price of share of select companies of auto sector as whole. The implications and limitations of study are also discussed.